‘Bandi’ as an Unknown Classical Poet - Mstafa, Umed Aziz (Zanco Journal of Human Sciences, 2024)
Looking back is the strength for the present and the foundation for in novation. Although Kurdish poets have moved away from the classical path for a long time and Kurdish poetry has passed through several other stages, this study shows that there are poets, even if they are individuals Nowadays, they compose classical poetry and follow the classical path the discovery of the works of a classical poet is now equally important in introducing them to Kurdish readers, writers and enriching the poetry of our national literature. Especially in Hiran town and Khoshnawti area. Because it still contains many raw materials that no one has realized or created, to reach out to, to rescue them from the frame work of oblivion and unknown and unwritten work, so this is considered the first academic work. It can be said that after a careful investigation and a lot of effort, we were able to obtain a handful of classical poems of the poet (Bandi) and make it the content of our research. Although Bandy is poems have not been collected in a book, this has led to a few pieces of poetry that do not exceed the fingertips. In this research, we have made the stages of the poet’s life and the characteristics of his poems, in terms of form and content, the essence of the research. We have followed a historical and descriptive approach to organize the work.